Effect of TiO2 whiskers on the microstructure and mechanical and dielectric properties of MgO ceramics. Issue 3 (1st February 2023) - Yuan, Qi; Wang, Sen; Hu, Wencai; Wang, Tao; Liu, Gaobin; Han, Xueyan; Guo, Feixiang; Fan, Yongheng
Abstract: Here, TiO2 (w)-containing MgO ceramics were sintered at 1450 °C using a solid-phase method, and the effect of TiO2 (w) addition on the sintering, dielectric, and mechanical properties of MgO ceramics was investigated. The results indicate that TiO2 (w) reacts with MgO during sintering to form a new phase, Mg2 TiO4, and a 'special' structure of Mg2 TiO4 surrounds the MgO grains. This structure contributes to the densification of the MgO ceramics during sintering, thereby improving the dielectric and mechanical properties. The dielectric constants of MgO ceramic samples with different TiO2 (w) additions fluctuated between 10.6 and 11.9, and the loss tangent values fluctuated between 1.3 × 10 -4 and 4.0 × 10 –4 ; when TiO2 (w) was added at 12 wt%, the relative density, flexural strength, fracture toughness, nanohardness, elastic modulus, and Vickers hardness of the sintered samples achieved a maximums of 97.4%, 221.0 MPa, 3.2 MPa m 1/2, 4.2 GPa, 383.1 GPa, and 1048.7 HV, respectively. The introduction of TiO2 (w) resulted in the formation of continuous and uniformly distributed intermediate phases inside the material, which improved the MgO ceramic densities, and dielectric and mechanical properties.